The Influence Of Online Communication Strategies On Purchase Intention Of Skincare Products In Generation Z - Marsach Adelia; Abdul Haeba Ramli; Erny Amriani Asmin; Zianneil T. Gecolea Gecolea (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The purpose of this study was to analyze the factors that influence online communication strategies in generation Z to buy beauty products that focus on the TikTok platform involving the variables ewom, influencer marketing, content marketing, attitudes, subjective norms, purchase intentions and purchasing behavior. This study is quantitative using a purposive sampling technique conducted through an online questionnaire to 140 respondents of skintific product consumers aged 17-27 years in Tangerang. The results showed that the ewom variable had a positive effect on purchase intentions, while influencer marketing and content marketing showed a positive effect on purchase intentions. Then attitudes and subjective norms were proven to have a positive effect on purchase intentions. In addition, purchase intentions also have a positive effect on purchasing behavior. Then purchase intentions provide an indirect effect between attitudes and purchasing behavior, purchase intentions provide an indirect effect between attitudes and purchasing behavior, purchase intentions provide an indirect effect between subjective norms and purchasing behavior. Purchase intention provides an indirect influence between influencer marketing and content marketing on purchasing behavior. The results of this study are expected to help develop marketing theory and business practices in the skincare industry and be a reference for future research. Keywords: ewom, influencer marketing, content marketing, attitude, subjective norms, purchase intention and purchase behavior.